Analisis Konsistensi Volume Output Pada Nozzle Barrel Mesin Mini Injeksi V-Line Menggunakan Material Plastik Polypropylene ExxonMobil AP03B - Bayu Prabandono; Alex Satria Wibawa; Mirza Yusuf; Agus Kurniawan; Aditya Nugraha (Universitas Muhammadiyah Yogyakarta, 2024)
One of the processes commonly used in making plastic goods is the injection molding process. Every process in injection molding has a very important role. A less-than-perfect process will result in defects or failure in the product. To reduce product defects, one of the processes that must be researched is the barrel purging process. The purging volume on the mini injection machine using the V-line method is inconsistent, as evidenced by the fact that if the purging waste, or what is usually called an avalanche is weighed, it will produce a non-uniform mass. This research uses a mini injection machine with the V-line method which has 2 main steps to carry out the plastic injection process; dosing and injecting. Unlike injection engines in general, this engine does not have a check-ring to withstand back pressure. This machine uses a shut-off system as a replacement for the check-ring role. This machine has never been subjected to a purging volume consistency testing process. The consistency of the purging volume greatly influences the product uniformity results. The research method used in this final assignment is direct. Data collection and test specimen collection will be taken directly on the mini injection machine using the V-line method. The steps taken in this research are planning, taking data, taking test specimens, processing test specimen data, and comparing test specimen data to obtain analysis results. The research results show that the mini V-line injection machine cannot support mass production, because increasing the screw rotation speed will affect the consistency of the volume of plastic that will be produced in the barrel, causing production to not run quickly and precisely.